Salt marsh vegetation change during a half-century of experimental nutrient addition and climate-driven controls in Great Sippewissett Marsh - I. Valiela; K. Chenoweth; J. Lloret; J. Teal; B. Howes; D. Goehringer Toner (Science of The Total Environment, 2023)

Test–retest reliability of arterial spin labelling for cerebral blood flow in older adults with small vessel disease - Lauren R. Binnie; Mathilde M. H. Pauls; Philip Benjamin; Mohani-Preet K. Dhillon; Shai Betteridge; Brian Clarke; Rita Ghatala; Fearghal A. H. Hainsworth; Franklyn A. Howe; Usman Khan; Christina Kruuse; Jeremy B. Madigan; et al. (Translational Stroke Research, 2022)
Cerebral small vessel disease (SVD) is common in older people and is associated with lacunar stroke, white matter hyperintensities (WMH) and vascular cognitive impairment. Cerebral blood flow (CBF) is reduced in SVD, particularly within white matter. Here we quantified test–retest reliability in CBF measurements using pseudo-continuous arterial spin labelling (pCASL) in older adults with clinical and radiological evidence of SVD (N=54, mean (SD): 66.9 (8.7) years, 15 females/39 males). We generated whole-brain CBF maps on two visits at least 7 days apart (mean (SD): 20 (19), range 7-117 days). Test–retest reliability for CBF was high in all tissue types, with intra-class correlation coefficient [95%CI]: 0.758 [0.616, 0.852] for whole brain, 0.842 [0.743, 0.905] for total grey matter, 0.771 [0.636, 0.861] for deep grey matter (caudate-putamen and thalamus), 0.872 [0.790, 0.923] for normal-appearing white matter (NAWM) and 0.780 [0.650, 0.866] for WMH (all p<0.001). ANCOVA models indicated significant decline in CBF in total grey matter, deep grey matter and NAWM with increasing age and diastolic blood pressure (all p<0.001). CBF was lower in males relative to females (p=0.013 for total grey matter, p=0.004 for NAWM). We conclude that pCASL has high test–retest reliability as a quantitative measure of CBF in older adults with SVD. These findings support the use of pCASL in routine clinical imaging and as a clinical trial endpoint. All data come from the PASTIS trial, prospectively registered at: https://eudract.ema.europa.eu (2015-001235-20, registered 13/05/2015), http://www.clinicaltrials.gov (NCT02450253, registered 21/05/2015).

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study - Michael A. P. Bloomfield; Yumeya Yamamori; Chandni Hindocha; Augustus P. M. Jones; Jocelyn L. L. Yim; Hannah R. Walker; Ben Statton; Matthew B. Wall; Rachel H. Lees; Oliver D. Howes; Valerie H. Curran; Jonathan P. Roiser; et al. (Psychopharmacology, 2022)
Rationale There is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. Objectives We sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotion-related measures to test cognitive-mechanistic models of its effects on anxiety. Methods We conducted a randomised, double-blind, placebo-controlled, crossover, acute oral challenge of 600 mg of CBD in 24 healthy participants on emotional processing, with neuroimaging (viewing emotional faces during functional magnetic resonance imaging) and cognitive (emotional appraisal) measures as well as subjective response to experimentally induced anxiety. Results CBD did not produce effects on brain responses to emotional faces and cognitive measures of emotional processing, or modulate experimentally induced anxiety, relative to placebo. Conclusions Given the rising popularity of CBD for its putative medical benefits, these findings question whether further research is warranted to investigate the clinical potential of CBD for the treatment of anxiety disorders.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Historic and Modern Approaches for the Discovery of Abandoned Wells for Methane Emissions Mitigation in Oil Creek State Park, Pennsylvania - Patricia M. B. Saint-Vincent; James I. Sams; Mumbi Mundia-Howe; Matthew D. Reeder; Garret A. Veloski; Natalie J. Pekney (Environmental Management, 2021)

Publisher Correction to: Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Leveraging a Landscape-Level Monitoring and Assessment Program for Developing Resilient Shorelines throughout the Laurentian Great Lakes - Donald G. Uzarski; Douglas A. Wilcox; Valerie J. Brady; Matthew J. Cooper; Dennis A. Albert; Jan J. H. Ciborowski; Nicholas P. Danz; Anne Garwood; Joseph P. Gathman; Thomas M. Gehring; Greg P. Grabas; Robert W. Howe; et al. (Wetlands, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

Replacement of Phragmites australis by Spartina alterniflora: The Role of Competition and Salinity - D. L. Medeiros; D. S. White; B. L. Howes (Wetlands, 2013)

Conifer DBMagic: a database housing multiple de novo transcriptome assemblies for 12 diverse conifer species - W. Walter Lorenz; Savavanaraj Ayyampalayam; John M. Bordeaux; Glenn T. Howe; Kathleen D. Jermstad; David B. Neale; Deborah L. Rogers; Jeffrey F. D. Dean (Tree Genetics & Genomes, 2012)

Glycemic index, glycemic load, and pancreatic cancer risk (Canada) - Stephanie A. N. Silvera; Thomas E. Rohan; Meera Jain; Paul D. Terry; Geoffrey R. Howe; Anthony B. Miller (Cancer Causes & Control, 2005)

Experimental investigation of taxon‐specific response of alkaline phosphatase activity in natural freshwater phytoplankton - K. Rengefors; K. C. Ruttenberg; C. L. Haupert; C. Taylor; B. L. Howes; D. M. Anderson (Limnology and Oceanography, 2003)
It is widely accepted that alkaline phosphatase activity (APA) is an efficient indicator of phosphate limitation in freshwater phytoplankton communities. In this study, we investigated whether the response in APA to phosphate limitation differs among the taxa in a mixed phytoplankton assemblage. We used the new enzyme‐labeled fluorescence (ELF) technique, which allows microscopic detection of phosphate limitation in individual cells of multiple species. The most prominent findings of this study were that alkaline phosphatase (AP) was induced in many, but not all taxa and that different taxa, as well as different cells within a single taxon, experienced different degrees of phosphate stress under the same environmental conditions. Our approach was to manipulate the limiting nutrient in a natural freshwater phytoplankton community by incubating lake water in the laboratory. We induced nitrogen (N) or phosphate limitation through additions of inorganic nutrients. Both the ELF assay and bulk APA indicated that the lake phytoplankton were not phosphate limited at the start of the experiment. During the experiment, several chlorophyte taxa (e.g., Eudorina and an unidentified solitary spiny coccoid) were driven to phosphate limitation when inorganic N was added, as evidenced by a higher percentage of ELF‐labeled cells relative to controls, whereas other chlorophyte taxa such as Actinastrum and Dictyosphaerium were not phosphate stressed under these conditions. In the phosphate‐limited treatments, little or no ELF labeling was observed in any cyanobacterial taxa. Furthermore, all taxa observed after the ELF labeling procedure (

Formation of two types of low-spin heme in horseradish peroxidase isoenzyme A2 at low temperature - B. D. Howes; A. Feis; C. Indiani; M. P. Marzocchi; G. Smulevich (JBIC Journal of Biological Inorganic Chemistry, 2000)

The relationship between dietary fat intake and risk of colorectal cancer: evidence from the combined analysis of 13 case-control studies - Geoffrey R. Howe; Kristan J. Aronson; Enrique Benito; Roberto Castelleto; Jacqueline Cornée; Stephen Duffy; Richard P. Gallagher; José M. Iscovich; Jiao Deng-ao; Rudolf Kaaks; Gabriel A. Kune; Susan Kune; et al. (Cancer Causes & Control, 1997)